Indonesia’s Global Maritime Axis Doctrine: Security Concerns and Recommendations - Dewi Santoso; Fadhillah Nafisah (Jurnal Hubungan Internasional, 2017)
Since President Joko Widodo’s administration begins, there has been a new reform forIndonesia’s maritime psyche. The President sees a huge potential in Indonesia’s maritimesector, especially due to its strong and consolidated domain around Indian and PacificOceans. Hence, he came up with an overarching concept of “Global Maritime Axis”,and set it as the main point of his administration. This so-called “Jokowi’s doctrine”fundamentally represents national vision and development agenda to rebuild the country’sidentity as a maritime nation, boosts its maritime culture, and expands its economy fromwhich Indonesians could prosper. This paper seeks to analyze the impact of Indonesia’smaritime vision in foreign and defense policy, specifically upon maritime diplomacy andresolutions of border disputes; maintenance of territorial integrity, maritime sovereignty,good order at sea, security over the outer islands; and safeguards over national resourcesand exclusive economic zones (EEZ). It then ends with examining recent maritime securitydevelopments, which fosters Indonesia’s position as a maritime power with considerablediplomatic influence on the world, and the opportunities therein.